ANALISIS METAKOGNISI SISWA BERBASIS LESSON STUDY FOR LEARNING COMMUNITY (LSLC) DITINJAU DARI GAYA KOGNITIF - Saiful Saiful; Hobri Hobri; Mohammad Tohir (Fakultas Tarbiyah Universitas Ibrahimy, 2020)
This research aims to analyze students' metacognition in learning mathematical problem solving based on Lesson Study for Learning Community (LSLC) if reviewed from reflective and impulsive cognitive styles. The research method employed in this research is descriptive qualitative. The data collection is done by observation, tests, interviews, think aloud and documentation. The test is given to 30 students when an open class in class VII of MTs Miftahul Hidayah. Based on the test results, students are grouped into two in reviewed from reflective and impulsive cognitive styles. Three students were selected from each group to be interviewed and deepened through a think-aloud technique. The form of data analysis is classified into induction and reduction theory. The results of this research indicates that 18 students (60%) have reflective cognitive styles and 12 students (40%) have impulsive cognitive styles. Reflective cognitive style students, the scores obtained are better by using a relatively long time and can do aspects of metacognition well. While the scores obtained by impulsive cognitive style students are lower with the use of the time that is relatively faster and unable to perform aspects of metacognition well.